THE EFFECT OF KIND BLOOD PARASITE INFECTION ON SOME PRODUCTIVE TRAITS IN TURKISH AWASSI SHEEP - & et al., Nasir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted  at the Ruminants Researches Station (25 km west of Baghdad) as well as the Directorate for Agricultural Researches / Ministry of Agriculture, as from the  Reproductive laboratory at the College of Agriculture/University of  Baghdad  from 01/03/2015 to 15 / 09/2015 on sample  94 awassi dams . In order to study effect infection on production traits to growth traits , The percentage of healthy dams was 70.21%, while the proportion of ewes was 29.79% and the differences between the two were highly significant (P